Reklama negatywna i wizerunkowa w odbiorze polskiego elektoratu - Olszanecka-Marmola, Agata (Political Preferences, 2015)
Negative and visual advertising in the reception of Polish electorate Growing professionalization and personalization of electoral campaigns have prompted political parties to concentrate on political image and negative campaigning. This tendency is mainly noticeable in TV advertisements. Presented article consists of two parts. The first one discusses the role of negative and image ads. The other part includes the results of research conducted by the author. The analysis shows that the vast majority of Polish electorate does not approve using of negative and image advertising. It can denote that voters are exhausted of permanent mutual attacks of two major Polish parties (Civic Platform, Law and Justice) and expect more issue-oriented politics. Key words: political advertising, advertising, negative ads, political image, image ads